Aminoglycoside Resistance Genes aph(2")-Ib and aac(6′)-Im Detected Together in Strains of both Escherichia coli and Enterococcus faecium - Chow, Joseph W. (American Society for Microbiology, 2001)
Escherichia coli SCH92111602 expresses an aminoglycoside resistance profile similar to that conferred by the aac(6′)-Ie-aph(2")-Ia gene found in gram-positive cocci and was found to contain the aminoglycoside resistance genes aph(2")-Ib and aac(6′)-Im (only 44 nucleotides apart). aph(2")-Ib had been reported previously in Enterococcus faecium SF11770. aac(6′)-Im had not been detected previously in enterococci and was found to be present also 44 nucleotides downstream from aph(2")-Ib in E. faecium SF11770. aph(2")-Ib and aac(6′)-Im are separate open reading frames, each with its own putative ribosome binding site, whereas aac(6′)-Ie-aph(2")-Ia appears to be a fusion of two genes with just one start and one stop codon. The deduced AAC(6′)-Im protein exhibits 56% identity and 80% similarity to the AAC(6′)-Ie domain of the bifunctional enzyme AAC(6′)-APH(2"). Our results document the existence of a member of the aph(2") family of genes in gram-negative bacteria and provide evidence suggesting the horizontal transfer of aph(2")-Ib and aac(6′)-Im as a unit between gram-positive and gram-negative bacteria.